2015
DOI: 10.1093/femsle/fnv218
|View full text |Cite
|
Sign up to set email alerts
|

Detection of psychrophilic and psychrotolerantClostridiumspp. in chilled fresh vacuum-packed meat using different PCR methods

Abstract: Since 1989, blown pack spoilage has been recognized as a special form of spoilage in vacuum-packed raw and cooked beef. However, only limited information concerning the occurrences of bacteria causing blown pack spoilage on chilled fresh meat is available. In this study, a total of 63 beef and 33 lamb commercially available samples from different countries and without any signs of spoilage were examined for contamination with psychrophilic and psychrotolerant Clostridium spp. using different PCR systems. In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…The isolated C. estertheticum strain from BPS pork showed β‐haemolysis on CBA. In the studies of Dorn‐In et al () and Bonke et al (), all strains of C. estertheticum showed β‐haemolysis on blood agar. Yang et al () showed that both C. estertheticum sub spp.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The isolated C. estertheticum strain from BPS pork showed β‐haemolysis on CBA. In the studies of Dorn‐In et al () and Bonke et al (), all strains of C. estertheticum showed β‐haemolysis on blood agar. Yang et al () showed that both C. estertheticum sub spp.…”
Section: Resultsmentioning
confidence: 92%
“…(2018) and Bonke et al (2016), all strains of C. estertheticum showed b-haemolysis on blood agar. Yang et al (2010b) showed that both C. estertheticum sub spp.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…O C. estertheticum ao contrário de outras bactérias do mesmo gênero, não produz toxinas sendo, porém, seus esporos encontrados em embalagens a vácuo resistindo ao pH normal da carne durante quatro semanas (COLLINS et al 1992, HELPS et al 1999, BRODA et al 2002, ADAM et al, 2013. Devido a dificuldades de isolamento e cultivo de C. estertheticum em meio de cultura, a forma mais segura de detecção do agente caracteriza-se pela extração do DNA seguido pelo uso de técnicas moleculares (BONKE et al, 2016).…”
Section: Fonte: Elaborada Pelos Autoresunclassified
“…Entretanto, difere bastante com o resultado encontrado por BONKE et al (2016), 34,4%. A diferença na positividade entre os resultados comparados é devida, provavelmente, à melhoria dos procedimentos no processo de higienização, os chamados sistemas de: "Boas Práticas de Fabricação" (BPF) e "Análise de Perigos e Pontos Críticos de Controle" (APPCC) que foram incorporados à rotina de limpeza e sanitização após a obtenção dos primeiros resultados.…”
Section: Fonte: Elaborada Pelos Autoresunclassified